Enhancing Mathematical Understanding of Fractions Through Image Media: A Study in Primary Education - Samritin; Fajar, Ahmad; Fadiarni; Safitri Tomia, Nur; Rasni; Mimin, Siti Nur; Adelia, Wa Ode Riska (Lembaga Riset dan Inovasi Masyarakat Madani, 2024)
This study investigates the impact of using image media on the mathematical ability of third-grade students in solving fractional story problems at SDN Palatiga. Using a quantitative experimental design, the study involved 30 students from class III (A) and 30 from class III (B). Descriptive tests and observation sheets, validated by experts and pre-tested, were used as research instruments. The findings reveal that while the post-test scores for the class using image media showed an average of 74.33 (with a highest score of 85 and a lowest of 65), the t-test result (sig. = 0.105) indicated no statistically significant difference between pre- and post-test scores. Despite the statistical insignificance, practical improvements in students' understanding were observed. These results suggest that image media has the potential to enhance student engagement and comprehension in solving fractional problems. However, further research with larger samples and extended interventions is recommended to validate these findings and explore broader applications of image media in mathematics education.